Decentralized Biogas Technology of Anaerobic Digestion and Farm Ecosystem: Opportunities and Challenges - Wang, Junye (Frontiers in Energy Research, 2014)
Long-term economic and environmental concerns have resulted in a great amount of research on renewable sources of biomass and bioenergy to replace fossil fuels in the past decades. Decentralized biogas technology is one of the most potential technologies of biomass and bioenergy by using agricultural waste materials (e.g., animal manure, crop straw and by-products from food industries) as feedstocks. By-products from biogas production, called digestate, are nutrient rich which could potentially be reused as green fertilizers in agriculture, thereby providing a sustainable substitute for synthetic fertilizers for ecosystem farm. Thus, the biogas production of anaerobic digestion (AD) is win-win option for livestock and crop producers to address issues of waste management and energy supply, and to avoid contamination of surface and ground waters and emissions of odors and greenhouse gases. In this paper, we review biogas production technology and then evaluate environmental effects of digestate used as fertilizer. Finally, we discuss issues of deployment of decentralized biogas technology for ecosystem farms. Economic and technological barriers still exist for large scale deployment of biogas technology. Two national scale deployments in China and Nepal showed that the operational status of biogas digesters is not optimal and up to 50% of plants are non-functional after a short operation period regardless of the social and economic factors. Main barriers are a wide variation of feedstocks and environmental conditions (e.g., temperature) over space and time. It becomes clear that the experimental conditions of the pilot plants need to be adjusted and calibrated to the local feedstocks and climate. Also, more research needs to be done in cold fermentation technology.